GLOBAL JUSTICE PROTEST EVENTS AND THE PRODUCTION OF KNOWLEDGE ABOUT DIFFERENCES - Daro, Vinci E. F. (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2009)
ABSTRACT. Recent social movement activities – in particular, transnationally-coordinated global justice mobilizations – require participants to work across substantial differences in languages, cultural backgrounds, political visions, and organizing traditions. Negotiating such differences is an active, adaptive, and learning-intensive process. In contrast to more institutionalized settings such as schools and workplaces, where tropes like “multiculturalism᾿ figure prominently in treatments of “difference,᾿ I argue that knowledge production in social movement settings cultivates a more intensely relational and dynamic disposition towards differences. LES ACTIONS REVENDICATRICES DE JUSTICE GLOBALE ET LA CRÉATION DE SAVOIR SUR LES DIFFÉRENCES RÉSUMÉ. Les activités récemment menées par les mouvements sociaux – plus spécifiquement, les mobilisations transnationales de justice globale – amènent les participants à collaborer au-delà de différences parfois substantielles de langues, origines culturelles, visions politiques et traditions d’organisation. La négociation de ces différences s’incarne dans un processus actif et nécessite un effort intense d’adaptation et d’apprentissage. Contrairement aux milieux institutionnels – écoles ou milieux de travail – où les rhétoriques telles que le multiculturalisme oriente de manière évidente la gestion des différences, je soutiens que la création de connaissances au sein des mouvements sociaux favorise une disposition dynamique et intensément relationnelle envers les différences.